2016
DOI: 10.1016/j.jtcvs.2016.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thrombosis in right internal jugular vein after percutaneous superior vena cava catheter insertion during cardiovascular surgery with cardiopulmonary bypass

Abstract: The incidence of percutaneous superior vena cava catheter-related thrombosis was higher than conventional central venous catheter-related thrombosis. Risk factors were age, superior vena cava catheter indwelling duration, and amount of transfusion platelet concentrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…In recent studies, the incidence of venous IJV thrombosis was reported as high; however, in our series, IJV thrombosis occurred in no patients. [14] Nonetheless, there are some limitations to this study. This study was conducted on a limited case group in a retrospective design.…”
Section: Discussionmentioning
confidence: 92%
“…In recent studies, the incidence of venous IJV thrombosis was reported as high; however, in our series, IJV thrombosis occurred in no patients. [14] Nonetheless, there are some limitations to this study. This study was conducted on a limited case group in a retrospective design.…”
Section: Discussionmentioning
confidence: 92%
“…Timsit [1] reported that the incidence of CRT was 33% in 208 CVCs inserted in medical/surgical ICUs, and CRT increased the incidence of catheter-related sepsis by 2.62 times. In cardiovascular surgical patients, Chung [3] reported that the incidence of CRT diagnosed by ultrasound was 56.2%, and the risk factors for CRT were age, duration of catheter placement, and transfused platelet volume. In our study, which is the first report on CRT in patients with both CVC and PAC insertion, CRT occurred in 78% of patients, which is higher than the frequency of CRT reported in previous studies on the sole use of CVC (11.7-75%) [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Central venous catheters (CVCs) and pulmonary artery catheters (PACs) are among the most important devices for the management of critically ill patients in intensive care units (ICUs). In addition to bleeding during catheter insertion and the associated infection, the formation of intravenous thrombi, known as catheter-related thrombosis (CRT) [1][2][3][4][5], has been reported as a common complication during the usage of these catheters. The major risk factors for CRT are hypercoagulability, stasis of blood flow, and endothelial injury, known as the Virchow triad [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Oh and colleagues 7 are the first to report the incidence of thrombus in large cannulas placed percutaneously in the RIJV for instituting cardiopulmonary bypass. Ultrasound of the RIJV was conducted on 123 patients immediately before insertion of a 21F cannula and at 24 and 48 hours subsequently.…”
mentioning
confidence: 99%